Social science production of Malaysian universities based on the scopus database: A centre-periphery analysis - Abdulra’uf, M.Y. (American Scientific Publishers, 2017)
This article examines the publication patterns of Malaysian social sciences and humanities in the last fifteen years (2000–2015) based on Scopus database. It is based on a bibliometric study of; (1) The Universities with highest output, (2) Publication growth in the last fifteen years (3) the Publication sources, and (4) the pattern of research collaborations. The Paper predicates its argument within the Centre-Periphery model of analysis. A Centre-Periphery Model suggests the division of the World of knowledge into the Centre (United States, United Kingdom, France, and Germany), and the Periphery, consisting of countries in the developing region such as Africa, Asia and Latin America. This model suggests greater dependence of the periphery on the centre, in terms of research collaboration, research publication, books, and Conferences. The scope of the paper is restricted on the patterns of Malaysian publications, collaborations in the last fifteen years. The data reveals the plausibility of dependency theory. However, it challenges its static (non-movement of the Periphery), and the linear view towards the centre (knowledge relationship with centre). Our data establishes that the globalisation of higher education has prompted the exponential growth of Malaysian social sciences in the last fifteen years, and has increased greater research collaborations, not only with the Centre, but with Countries in the Periphery. Similarly, the impressive performance of Malaysian scholarly Journals challenges the thesis of academic dependency. The paper calls for greater internationalisation of Malaysian social science Journals. © 2017 American Scientific Publishers. All rights reserved.